Effect of ankle sprain on postural control and electrical activity of selected muscles after single-leg jump landing task - Maleki, Behnaz; Mantashloo, Zahed; Salehi, Shahin; Abedi yekta, Amir hosein (Novelty in Biomedicine, 2019)
Background: Ankle joint plays an important role in restoring the balance of individuals. Ankle sprain injury effects on balance of affected individuals. The changes in the postural control and activity of the ankle muscle, because of ankle sprain, can put the patients at reinjure risk and lower extremity injuries, especially during dynamic activities. The aim of this study was to investigate the electrical activity of ankle joint stabilizer muscles and postural stability after single-leg jump landing in individuals with ankle sprain. Materials and Methods: In this cross-sectional study, 30 non-athletic students were participated. They were divided in two groups of 15 people, in the form of accessible and purposeful. Subjects was asked to land on a force plate with Single-leg, by at least 80% of their maximum jump. The com-cop changes assessment was used as an indicator for postural control evaluation. After jump landing, muscles activity was recorded on the ankle joint by surface electromyography (EMG) device. MATLAB software was used to analyze data, and MANOVA test was performed to compare two groups. Results: The results showed a significant reduction in EMG of soleus, gastrocnemius, and peroneus longus muscles (p=0.03, p=0.01 and p=0.006 respectively). Tibialis anterior activity significantly increased (p=0.001) in patient group than to healthy group. Postural control was significantly lower in patient group than healthy group, in all directions (p=0.00 and p=0.00 respectively). Conclusion: Decreased postural control indicates changes in EMG of the stabilizer muscles of this joint in people with ankle sprain injury.